Health-related Quality of Life (HR-QOL) and Chronic Health Conditions in Survivors of Childhood Acute Myeloid Leukemia (AML) with Down Syndrome (DS): A Report From the Children's Oncology Group. Issue 1 (January 2017) - Schultz, Kris Ann P.; Chen, Lu; Kunin-Batson, Alicia; Chen, Zhengjia; Woods, William G.; Gamis, Alan; Kawashima, Toana; Oeffinger, Kevin C.; Nicholson, H. Stacy; Neglia, Joseph P.
Abstract : Survival rates for children with Down syndrome (DS) and acute myeloid leukemia (AML) are high; however, little is known regarding the health-related quality of life (HR-QOL) of these survivors. Individuals who survived ≥5 years following diagnosis of childhood AML were invited to complete parent or patient-report surveys measuring HR-QOL and chronic health conditions. In total, 26 individuals with DS had a median age at diagnosis of 1.8 years (range, 0.77 to 10.9 y) and median age at interview of 15 years (range, 8.3 to 27.6 y). Participants with DS and AML were compared with AML survivors without DS whose caregiver completed a HR-QOL survey (CHQ-PF50). In total, 77% of survivors with DS reported ≥1 chronic health condition compared with 50% of AML survivors without DS ( P =0.07). Mean physical and psychosocial QOL scores for children with DS and AML were statistically lower than the population mean, though not discrepant from AML survivors without DS. Although the overall prevalence of chronic health conditions in survivors with DS is higher than in survivors without DS, prior studies of children with DS have reported similarly high rates of chronic health conditions, suggesting that AML therapy may not substantially increase this risk.